Creative Thinking Process of Prospective Elementary Education Teacher Students Based on Field Independent Cognitive Styles and Self-Efficacy in Solving Contextual Problems - Suprapti, Endang; Siswono, Tatag Yuli Eko Siswono; Manuharawati; Hidayatullah, Achmad Hidayatullah; Wijaya, Armeria Wijaya (Journal of Mathematical Pedagogy (JoMP), 2024)
This study aims to describe the creative thinking process of prospective elementary school teachers based on independent field cognitive style and self-efficacy in solving contextual problems. This qualitative-exploratory study involved two prospective elementary school teachers who had independent field cognitive style and self-efficacy. Data collection was conducted through task-based interviews and analysis using interactive methods consisting of data condensation, data presentation, data interpretation and verification. The results showed that prospective elementary school teachers with independent field cognitive style and high self-efficacy had better creative thinking processes than prospective elementary school teachers with independent field cognitive style and low self-efficacy. Prospective elementary school teachers with independent field cognitive style and high self-efficacy in synthesizing ideas understood information well, and met the criteria for creative thinking in terms of fluency, flexibility and novelty. Meanwhile, prospective elementary school teachers with independent field cognitive style and low self-efficacy did not see the provisions in the questions given well, and only met the fluency criteria aspect.